2022
DOI: 10.2147/ppa.s375037
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Routines and Rituals on Burden of Treatment, Patient Training, Cognitive Load, and Anxiety in Self-Injected Biologic Therapy

Abstract: Background: Self-injection of biologics is a mainstay of chronic disease treatment, yet the process of self-injection often causes persistent apprehension and anxiety, distinct from needle phobia. While literature alludes to the role that routines and rituals play in self-injection, there is no comprehensive study on the routines and rituals self-injectors employ, nor of the process by which they are discovered and ingrained. Methods: We conducted a mixed-method, observational pilot ethnography study of 27 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“… 47 Besides supporting the use of the new MTX autoinjector, the guidance may be an occasion to improve patient education which is a strong predictor of adherence. 48 , 49 In general, the availability of various devices is advantageous to meet the individual needs of different patients. 17 , 42 , 50 However, switching back and forth should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“… 47 Besides supporting the use of the new MTX autoinjector, the guidance may be an occasion to improve patient education which is a strong predictor of adherence. 48 , 49 In general, the availability of various devices is advantageous to meet the individual needs of different patients. 17 , 42 , 50 However, switching back and forth should be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…Coyne et al reported that device training based on adult learning principles, routines, and rituals and at-home practice with a device trainer may reduce anxiety and unnecessary experimentation and improve injection therapy compliance. 31 These device trainers can be well-informed MS nurses and can provide support to pwMS to help them cope with their needle-related fears. While pwMS can be trained on the self-injection technique, routines and rituals are mostly selfdiscovered by the pwMS, and when these are anchored with timely guidance and continual educational support, they may help pwMS gain more confidence regarding the self-injection process.…”
Section: Discussionmentioning
confidence: 99%
“…While pwMS can be trained on the self-injection technique, routines and rituals are mostly selfdiscovered by the pwMS, and when these are anchored with timely guidance and continual educational support, they may help pwMS gain more confidence regarding the self-injection process. 31 Since MS nurses typically have more frequent clinical contact with pwMS than physicians, they can play a crucial role in educating pwMS about the disease and treatment they are receiving. This survey allowed us to understand the MS nurses' perspective on the key features of the RebiSmart 3.0 device that pwMS should be given additional information about that may potentially facilitate a smooth transition to it from their existing device or to start it as their first device.…”
Section: Discussionmentioning
confidence: 99%
“…[17] Coyne et al reported that device training based on adult learning principles, routines, and rituals and athome practice with a device trainer may reduce anxiety and unnecessary experimentation and improve injection therapy compliance. [23] These device trainers can be well-informed MS nurses and can provide support to pwMS to help them cope with their needle-related fears. While pwMS can be trained on the self-injection technique, routines and rituals are mostly self-discovered by the pwMS, and when these are anchored with timely guidance and continual educational support, they may help pwMS gain more con dence regarding the self-injection process.…”
Section: Discussionmentioning
confidence: 99%
“…While pwMS can be trained on the self-injection technique, routines and rituals are mostly self-discovered by the pwMS, and when these are anchored with timely guidance and continual educational support, they may help pwMS gain more con dence regarding the self-injection process. [23] Since MS nurses typically have more frequent clinical contact with pwMS than physicians, they can play a crucial role in educating pwMS about the disease and treatment they are receiving. This survey allowed us to understand the MS nurses' perspective on the key features of the RebiSmart 3.0 device that pwMS should be given additional information about that may potentially facilitate a smooth transition to it from their existing device or to start it as their rst device.…”
Section: Discussionmentioning
confidence: 99%